The impact of a novel Chinese yam-derived polysaccharide on blood glucose control in HFD and STZ-induced diabetic C57BL/6 mice. Issue 5 (16th February 2022) - Feng, Xiaojuan; Zhang, Qian; Li, Jingyao; Bie, Nana; Li, Chenjing; Lian, Rui; Qin, Liehao; Feng, Yihua; Wang, Chunling
Abstract : A Chinese yam polysaccharide possess a triple helix structure and has hypoglycemic activity. The mechanism of regulating blood glucose may be related to the PI3K/Akt signaling pathway in the livers of diabetic mice. Abstract : Chinese yam, as a kind of traditional "medicine and food homologous food" in Asia, could assistance to digestion, nourish the lungs and relieve cough. Some research also suggested that Chinese yam could prevention of hyperglycemia, but the specific mechanism of action was not clear. In this paper, an acidic polysaccharide (CYPB) was isolated from Chinese yam with the molecular weight of 1.55 × 10 2 kDa. The determination of the monosaccharide composition of CYPB with ion chromatography showed that CYPB was composed of rhamnose, glucose, arabinose, galactose, glucose, xylose and glucuronic acid with the ratio of 6 : 3.73 : 7.31 : 10.95 : 4.56 : 1. The structural analysis indicated that the CYPB contain 1 → 3, 1 → 4, 1 → 2, 1 → 6 and 1 → 3, 6 glycoside bonds. The experimental results of diabetic mice model induced by high-fat diet (HFD) and streptozocin (STZ) indicated that CYPB could improve clinical symptoms and alleviate the glucose tolerance damage symptoms effectively. The underlying mechanism of regulate blood glucose of CYPB may be related to improve the ability of synthesize glycogen, insulin resistance and reduce gluconeogenesis by regulating the expression of InsR, PI3K, Akt and FoxO3, GLUT4 proteins in PI3K/Akt signaling pathway in T2DM mice.